Stolephorus babarani, a new species of anchovy (Teleostei: Clupeiformes: Engraulidae) from Panay Island, central Philippines - Hata, Harutaka; Lavoué, Sébastien; Motomura, Hiroyuki (Zootaxa, 2020)
The new anchovy Stolephorus babarani n. sp. is described on the basis of 26 specimens collected from Panay Island, central Philippines. The new species closely resembles Stolephorus bataviensis Hardenberg 1933 and Stolephorus baweanensis Hardenberg 1933, all these species having a long upper jaw (posterior tip extending beyond posterior margin of preopercle), and numerous dusky spots on the suborbital area (in adults), snout and lower jaw tip. However, the new species differs from S. bataviensis by usually having the posterior tip of the depressed pelvic fin not reaching to vertical through the dorsal-fin origin (vs. extending beyond vertical through dorsal-fin origin), a shorter head (23.9–25.5% of standard length vs. 25.3–28.0%), and a greater distance between the dorsal-fin origin and pectoral-fin insertion (D–P1; 133.9–151.8% of head length vs. 109.9–136.3%). Stolephorus babarani is distinguished from S. baweanensis by having a shorter snout (3.6–3.9% of standard length vs. 3.8–4.6%). Moreover, the new species can be distinguished from S. bataviensis and S. baweanensis by higher gill raker counts on the first and second gill arches (16–18 + 21–23 and 10–13 + 18–21, respectively, vs. 14–17 + 19–22 and 9–12 + 17–20 in S. bataviensis and 14–17 + 19–22 and 9–12 + 17–21 in S. baweanensis). Stolephorus babarani is separated by 5.3% and 10.7% mean p-distances in the mitochondrial COI from S. baweanensis and S. bataviensis, respectively.